1996
DOI: 10.1002/(sici)1097-0215(19961127)68:5<637::aid-ijc14>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-interleukin-6 receptor antibody prevents muscle atrophy in colon-26 adenocarcinoma-bearing mice with modulation of lysosomal and ATP-ubiquitin-dependent proteolytic pathways

Abstract: Progression of skeletal muscle atrophy is one of the characteristic features in cancer patients. Interleukin-6 (IL-6) has been reported to be responsible for the loss of lean body mass during cancer cachexia in colon-26 adenocarcinoma (C-26)-bearing mice. This study was carried out to elucidate the intracellular proteolytic pathways operating in skeletal muscle in C-26-bearing mice, and to examine the effect of anti IL-6 receptor antibody on muscle atrophy. On day I 7 after tumor inoculation, trocnemius muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
76
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 26 publications
(11 reference statements)
7
76
0
Order By: Relevance
“…4 In agreement with this finding, we observed that administration of C. rhizoma prevented loss of gastrocnemius muscle in colon 26/clone 20 -bearing mice and decreased IL-6 levels. Tisdale 1 proposed that IL-6 may be a marker rather than an actual mediator of cancer cachexia since direct administration of this cytokine to experimental animals failed to induce cachexia and Hussey et al 22 observed a relation between proteolysis-inducing factor (PIF) and cachexia in colon 26/clone 20 -transplanted mice.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…4 In agreement with this finding, we observed that administration of C. rhizoma prevented loss of gastrocnemius muscle in colon 26/clone 20 -bearing mice and decreased IL-6 levels. Tisdale 1 proposed that IL-6 may be a marker rather than an actual mediator of cancer cachexia since direct administration of this cytokine to experimental animals failed to induce cachexia and Hussey et al 22 observed a relation between proteolysis-inducing factor (PIF) and cachexia in colon 26/clone 20 -transplanted mice.…”
Section: Discussionsupporting
confidence: 87%
“…1,2 IL-6, a mediator produced by tumors or the host as a result of tumor-host interaction, is considered to play an important role in cancer-induced cachexia, suggesting that downregulation of IL-6 levels may improve cachexia or malnutrition in cancer patients. [3][4][5][6] Indeed, an anti-IL-6 receptor antibody has been shown to prevent cancer-induced cachexia in a rodent model. 4 Also, medroxyprogesterone acetate (MPA), a synthetic progesterone derivative, has anticachectic activity, likely due in part to the suppression of IL-6 secretion from tumor cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When placed in mice, the C26 adenocarcinoma cell line form tumors which secrete proinflammatory cytokines. IL-6 was initially identified as a prominent player in C26-induced cachexia using anti-IL-6 antibodies, but later studies also identified TNFα and IL-1 [32,76], paralleling human cancer cachexia [17]. While all these cytokines interact with their own unique receptors on striated muscle, each receptor converges on the activation of the transcription factor NF-κB to induce skeletal muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotally, the use of α-3 omega fatty acids (eicosapentaenoic acid) [52] and thalidomide (potent anti-TNF activity) have been reported [48]. Experimentally, glucocorticoids, aspirin [63], indomethacin [35,79], methotrexate [60], and celecoxib [23], all have been shown to have some efficacy, which are believed to be effective, in part, due to their ability to inhibit NF-ĸB activity [10,32,73,78]. However, these agents are neither potent nor selective for the NF-ĸB pathway.…”
Section: Discussionmentioning
confidence: 99%